Pengaruh Harga, Kualitas Dan Merek Produk Thrifting Terhadap Keputusan Pembelian Di Pasar Sambu Kota Medan - Sihombing, Erika Juliana; Sianturi, Charles M.; Rajagukguk, Jonson (Research and Community Service UNIVERSITAS KALBIS, 2025)
The purpose of this research is to measure the influence of price, quality and brand of thrifting products on purchasing decisions by students at Sambu Market, Medan City. This research uses quantitative methods with non-probability sampling techniques and a purposive sampling approach with a sample size of 100 respondents. The data collection technique was carried out by distributing questionnaires to students with thrifting purchases no later than the last year. Data were analyzed using multiple regression analysis which began with tests of validity, reliability, classical assumptions, coefficient of determination, F test and t test which were carried out using SPSS version 25. Based on the partial t test and simultaneous F test, it is known that the three independent variables Price, Quality and Brand have a positive and significant effect on thrifting purchasing decisions by students at Sambu Market, Medan City. Based on the coefficient of determination R2, it is known that the three independent variables explain data variability of 0.761% in purchasing decisions for thrifting products.